Numerical Simulation of Air conditioning Vehicle Using Computational Fluid Dynamics - Hanqing Wang; Liping Xiang (2009 Asia-Pacific Power and Energy Engineering Conference, 2009)
By the steady state incompressible Reynolds-averaged Navier-Stokes equations, turbulence model, the finite volume method with interlacing of discretization, the three-dimension airflow and temperature fields inside a passenger vehicle are calculated numerically. The solar radiation and body heat are additional source term of energy equation, the influence of passenger and solar radiation on airflow and temperature fields is investigated. The results show that existing supply modes make the superior flow distribution homogeneous, body heat has much influence on airflow and temperature fields and solar radiation has little influence on airflow field, but much influence on temperature field. According to the standard QCn29008.9-1991, the experiment is carried out in the air-conditioned vehicle, which verify the correctness of numerical simulation. It is also shown that the prediction results of airflow and temperature to be used for evaluating the thermal comfort in the design procedure.